177k views
0 votes
Find missing term.x/x2-4x+4-x/x2-3x+2= ?/(x-2)2(x-1)

1 Answer

6 votes

Answer:

-3x

Explanation:

x x

----------------- - --------------------

x^2 -4x + 4 x^2-3x+2

x x

= ---------------- - --------------------

(x -2)^2 (x - 2)(x - 1)

x (x-1) - x(x +2)

= ----------------------------

(x -2)^2 (x - 1)

x^2 -x -x^2 - 2x

= --------------------------

(x -2)^2 (x - 1)

-3x

= -----------------------

(x -2)^2 (x - 1)

Therefore; the missing term is -3x

User Kwebble
by
5.0k points